(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Point absorber wave energy converters (WECs) are a promising solution for harnessing ocean energy due to their compact size, design simplicity, and potential for high energy capture efficiency. However, traditional modeling approaches often rely on single-degree-of-freedom motion and linear power take-off (PTO) systems, which can lead to inaccuracies in predicting power performance, hydrodynamic interactions, and structural loads. These limitations can result in suboptimal design choices and reduced efficiency, in both, structural and energy performance terms. To address these challenges, this study employs a two-degree-of-freedom time-domain model based on direct integration to support both performance evaluation and structural analysis of a point absorber WEC. The model incorporates nonlinear PTO component and enables numerical simulations by adopting customized sea surface elevation time series to effectively represent realistic wave excitation forces. Through dynamic load assessments, the study provides key insights into optimal floater geometry, and supporting structure design to enhance reliability, survivability, and overall efficiency. Furthermore, the potential for significantly reducing material costs—by up to 90%—and cutting production time by a factor of 20 is discussed through the application of advanced manufacturing technologies. Conclusions contribute to the development of more cost-effective, scalable, and structurally resilient wave energy converters, paving the way for viable commercialization and reliable deployment in the ocean.